Adherence to treatment with adalimumab, golimumab and ustekinumab in patients with inflammatory bowel disease - María Calvo-Arbeloa; Ana María Insausti-Serrano; Amaya Arrondo-Velasco; María Teresa Sarobe-Carricas (Elsevier, 2020)
Objective: Inflammatory bowel disease comprises a group of chronic relapsing inflammatory disorders affecting the bowel. In the last decade, the advent of biological drugs brought about a drastic change in the treatment of the disease. Adalimumab, golimumab and ustekinumab are three biologic agents that patients can self-administer subcutaneously after collecting them from the pharmacy department. However, for the treatment to be effective, adherence is paramount. The purpose of the present study is to evaluate adherence in patients who collected all three drugs from the dispensary of a tertiary care hospital. Method: A cross-sectional observational analysis was carried out of patients who had been receiving treatment with adalimumab, golimumab and ustekinumab for at least four months. The medication possession ratio was calculated based on information extracted from the pharmacy dispensing records. Patients with a ratio ≤ 85% were enrolled in the study and asked to respond to Morisky-Green Medication Adherence Questionnaire. Results: One-hundred and seventy-eight patients were included, of whom 60.1% (107) were male and 30.9% (55) had been treated previously with other biologics. According to the pharmacy dispensing records, mean adherence was 91.79%, with 45 patients (25.28%) classified as scarcely compliant (≤ 85%). The Morisky-Green Medication Adherence Questionnaire revealed that carelessness about administering the drug at the right time and forgetfulness were the main reasons for therapeutic non-adherence. Female sex (odds ratio 0.42; p = 0.013) and lengthy treatments (p = 0.002) were associated to lower adherence rates. Conclusions: Although most patients in the studied population were seen to be compliant, low levels of adherence were observed in a number of patients who would benefit from interventions aimed at boosting their adherence. It must be said, however, that the statistical power of this study should be enhanced in order to increase the significance of the results obtained.